HAIRY MERISTEM with WUSCHEL confines CLAVATA3 expression to the outer apical meristem layers - Zhou, Yun (Science, 2018)
The control of the location and activity of stem cells depends on spatial regulation of gene activities in the stem cell niche. Using computational and experimental approaches, we have tested, and found support for, a hypothesis for gene interactions that specify the Arabidopsis apical stem cell population. The hypothesis explains how the WUSCHEL gene product, synthesized basally in the meristem, induces CLAVATA3-expressing stem cells in the meristem apex, but, paradoxically, not in the basal domain where WUSCHEL itself is expressed. The answer involves the activity of the small family of HAIRY MERISTEM genes, that prevent the activation of CLAVATA3, and which are expressed basally in the shoot meristem. One Sentence Summary: The domain of stem cells in the Arabidopsis shoot apical meristem is founded on WUS expression but bounded by HAM expression.